A combination of topical and systemic administration of brimonidine is neuroprotective in the murine optic nerve crush model. - Ruta Maciulaitiene; Giedrius Kalesnykas; Dainius Haroldas Pauza; Ingrida Januleviciene (PLoS ONE)
Glaucoma is a multifactorial optic neuropathy that primarily affecting retinal ganglion cells (RGC). Brimonidine is an intraocular pressure-lowering drug with reported neuroprotective properties. This study aimed to compare the neuroprotective effects of topical and intraperitoneal (IP) brimonidine on RGCs from different retinal segments in a murine optic nerve crush (ONC) model. Methods forty-one Balb/c mice underwent unilateral ONC and were divided into three study groups: fifteen animals received saline drops twice per day and two additional IP injections of saline; fourteen mice received brimonidine drops twice per day; and 12 mice received brimonidine eye drops twice per day and two additional IP brimonidine injections. Animals were sacrificed seven days post-ONC, and immunohistochemical staining of retinal whole mounts was performed using neuronal NeuN and GFAP staining. Microscopic pictures of the central, middle, and peripheral regions of the retina were taken. The density of the retinal cells was assessed. Results The total RGC density after ONC and RGC densities in all retinal eccentricities were significantly higher in the brimonidine eye drop and IP combination treatment group than in the saline drop + saline IP, and brimonidine drop treatment groups. Conclusions brimonidine eye drops supplemented with IP brimonidine injections improved RGC survival in a preclinical model of ONC.